Talleres de ritmos y danzas originarias del Ecuador como estrategia didáctica para la afirmación de la identidad nacional en niños de 5 a 7 años de edad. - Cachimuel Chiza, María Cristina (2014)
The investigation and research of the workshops on rhythms and dances comes from the need to know more about the cultural heritage of the country, as all these issues are not taken into account within the educational scope especially for boys and girls, ages 5 to 7, who have limited exposure to the customs and traditions that come from each corner of Ecuador. These need to be rescued in order to endure in the collective memory and to continue to transmit for generations. The work contains information about the development of the child between the ages of 5 to 7 and the four scopes, such as basic physical, cognitive, language, and socio-affective development. These should be integrated in order to be able to know and work with the child. It is also necessary to define the following terms directly related to subjects such as intercultural and national identity and education in order to have a clear picture about these topics of interests for the project, as an important part of the work is the explanation of nine Ecuadorian rhythms which have arisen from the need to know the rich culture and protect it. Finally comes the overall project development goals and specifically the proposal that consists of nine workshops which contain rhythms and dances chosen for this project, the methodology, materials and resources used in the development of the workshops, also the results obtained from the application and evaluation.